2012
DOI: 10.14350/rig.32468
|View full text |Cite
|
Sign up to set email alerts
|

Estudio del confort térmico en la ciudad de São Paulo utilizando el modelo ENVI-MET

Abstract: En este estudio se analizó la comodidad termal en distintas áreas en la ciudad de São Paulo. Dos áreas diferentes fueron seleccionadas, densamente construido (Consolação) y el otro fue en el Parque de Estado de Ipiranga (FISP), un área con solo unos edificios e impermeabilidad reducida. Un microclimático ENVI - encontrado fue usado para simular la atmósfera superficial de interacción en el ambiente urbano. La resolución del modelo está entre 0.5 y 10 m. Este modelo fue desarrollado por Bruse y Fleer (1998) y B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, further studies must be conducted in other climate zones to understand the behavior of UWG in the specific zones. Additionally, this software considers the canyon as one homogenous entity [39,40]. Table 7 that shows the difference between the urban data and the main scenarios that are considered in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further studies must be conducted in other climate zones to understand the behavior of UWG in the specific zones. Additionally, this software considers the canyon as one homogenous entity [39,40]. Table 7 that shows the difference between the urban data and the main scenarios that are considered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 shows a typical urban canyon with the factors included in the UWG calculation (materials of the buildings, road, vegetation, AH due to traffic). Detailed information about the code is given in the annex section [24,30,40,41]. Figure 5.…”
Section: Residential Commercial Offices Restaurant Hotel Hospital Commentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that the building layout patterns' orientation with respect to wind has a significant effect on both the wind environment and thermal comfort, and when the longer facade of the building is parallel to the prevailing wind direction, the wind speed at the edges of the building increases. Carfan et al [21] studied the wind environment and thermal comfort in both a densely built district and a city park using ENVI-met software. They showed that the wind speed of the high building density area is lower, and the predicted mean vote (PMV) value of both study areas is nearly the same.…”
Section: Introductionmentioning
confidence: 99%
“…This software has previously been used in combination with aerial thermography to calibrate simulated models comparing urban surface temperatures (Fabbri and Costanzo, 2020). For calculating T MRT, it has also been widely used and validated by comparing the results with both other simulation tools and conventional methods Naboni et al, 2017;Gál and Kántor, 2020;Claudia Carfan, 2020).…”
Section: Microclimate Urban Simulation Verification Of T Mrtmentioning
confidence: 99%